Sn-seeded GaAs nanowires grown by MOVPE. (18th April 2016) - Sun, Rong; Vainorius, Neimantas; Jacobsson, Daniel; Pistol, Mats-Erik; Lehmann, Sebastian; Dick, Kimberly A
Abstract: It has previously been reported that in situ formed Sn nanoparticles can successfully initiate GaAs nanowire growth with a self-assembled radial p–n junction composed of a Sn-doped n-type core and a C-doped p-type shell. In this paper, we investigate the effect of fundamental growth parameters on the morphology and crystal structure of Sn-seeded GaAs nanowires. We show that growth can be achieved in a broad temperature window by changing the TMGa precursor flow simultaneously with decreasing temperature to prevent nanowire kinking at low temperatures. We find that changes in the supply of both AsH3 and TMGa can lead to nanowire kinking and that the formation of twin planes is closely related to a low V/III ratio. From PL results, we observe an increase of the average luminescence energy induced by heavy doping which shifts the Fermi level into the conduction band. Furthermore, the doping level of Sn and C is dependent on both the temperature and the V/III ratio. These results indicate that using Sn as the seed particle for nanowire growth is quite different from traditionally used Au in for example growth conditions and resulting nanowire properties. Thus, it is very interesting to explore alternative metal seed particles with controllable introduction of other impurities.